A model of the factors predicting English language teacher immunity: A path analysis - Rahimpour, Hadi; Amirian, Seyed Mohammad Reza; Adel, Seyed Mohammad Reza; Zareian, Gholam Reza (Universitas Pendidikan Indonesia, 2020)
Language teacher immunity, recently put forth by Hiver and Dornyei (2015), refers to â€œa robust armoring system that emerges in response to high-intensity threats and allows teachers to maintain professional equilibrium and instructional effectivenessâ€ (Hiver, 2017, p. 669). Due to the pure novelty of this construct, its significance to the practice of teaching and rarity of research on it, the present study aimed to develop a model on the predictors of this newly-developed concept. Based on the theories in the related literature, a model was proposed in which four traits of six HEXACO personality traits, job insecurity, and reflective teaching were considered as predicting factors. Through running Path Analysis using AMOS with Maximum Likelihood Estimate on the quantitative data obtained from 483 English language teachers from Iran, a revised model was obtained in which agreeableness, extroversion and emotionality were proved to have effects on language teacher immunity indirectly through job insecurity and reflective teaching which had direct effects on it. The strongest paths were from Job Insecurity (JI) to Reflective Teaching (RT) and Language Teacher Immunity (LTI) with considerable negative regression weights meaning that JI can have negative effects on both of them. The findings of the current research provide implications for both teachers and teacher trainers, highlighting the predictors of teacher immunity.